Promotion of tumor angiogenesis and growth induced by low-dose antineoplastic agents via bone-marrow-derived cells in tumor tissues - You, Huining; Zhao, Peipei; Zhao, Xue; Zheng, Qiaowei; Ma, Wenbing; Cheng, Kai; Li, Min; Kou, Jianrong; Feng, Weiyi (Frontiers in Pharmacology, 2024)
Background: More research is needed to solidify the basis for reasonable metronomic chemotherapy regimens due to the inconsistent clinical outcomes from studies on metronomic chemotherapy with antineoplastic agents, along with signs of a nonlinear dose-response relationship at low doses. The present study therefore explored the dose-response relationships of representative antineoplastic agents in low dose ranges and their underlying mechanisms. Methods: Cyclophosphamide (CPA) and 5-fluorouracil (5-Fu) were employed to observe the effects of the frequent administration of low-dose antineoplastic agents on tumor growth, tumor angiogenesis, and bone-marrow-derived cell (BMDC) mobilization in mouse models.The effects of antineoplastic agents on tumor and endothelial cell functions with or without BMDCs were analyzed in vitro. Results: Tumor growth and metastasis were significantly promoted after the administration of CPA or 5-Fu at certain low dose ranges, and were accompanied by enhanced tumor angiogenesis and proangiogenic factor expression in tumor tissues, increased proangiogenic BMDC release in the circulating blood, and augmented proangiogenic BMDC retention in tumor tissues.Low concentrations of CPA or 5-Fu were found to significantly promote tumor cell migration and invasion, and enhance BMDC adhesion to endothelial cells in vitro.These results suggest that there are risks in empirical metronomic chemotherapy using low-dose antineoplastic agents and the optimal dosage and administration schedule of antineoplastic agents need to be determined through further research.